GALACTOSE METABOLISM IN ZEA-MAYS ROOT TISSUES OBSERVED BY P-31-NMR SPECTROSCOPY - Loughman, B; Ratcliffe, R; Schwabe, J (1988)
In vivo 31P-nuclear magnetic resonance (NMR) spectroscopy was used to monitor the metabolism of d-galactose in excised root tissues from maize (Zea mays) seedlings. The accumulation of galactose 1-phosphate and uridinediphosphogalactose (UDP-gal) in the tissue was correlated with changes in the glucose 6-phosphate, cytoplasmic Pi, vacuolar Pi and NTP levels. NMR revealed a complicated time dependence for these metabolites with the galactose 1-phosphate signal going through a maximum after the NTP level had gone through a minimum. Many of the spectroscopic changes could be understood by viewing galactose as a sink for Pi and by supplying external Pi it was possible to modify the tissue response to galactose. Increasing the external galactose concentration increased the ratio of galactose 1-phosphate to UDP-gal in the loaded tissue whereas the protein synthesis inhibitor cycloheximide, which caused a marked increase in the NTP signals, reduced the ratio. The results suggest that the assimilation of galactose is limited by the slow metabolism of UDP-gal. © 1989.